The emergence of YMDD mutants precedes biochemical flare by 19 weeks in lamivudine-treated chronic hepatitis B patients: an opportunity for therapy reevaluation - França,P.H.C. (2007)
Given the loss of therapeutic efficacy associated with the development of resistance to lamivudine (LMV) and the availability of new alternative treatments for chronic hepatitis B patients, early detection of viral genotypic resistance could allow the clinician to consider therapy modification before viral breakthrough and biochemical relapse occur. To this end, 28 LMV-treated patients (44 ± 12 years; 24 men), on their first therapy schedule, were monitored monthly at four Brazilian centers for the emergence of drug resistance using the reverse hybridization-based INNO-LiPA HBV DR assay and occasionally sequencing (two cases). Positive viral responses (HBV DNA clearance) after 6, 12, and 18 months of therapy were achieved by 57, 68, and 53% of patients, while biochemical responses (serum alanine aminotransferase normalization) were observed in 82, 82, and 53% of cases. All viral breakthrough cases (N = 8) were related to the emergence of YMDD variants observed in 7, 21, and 35% of patients at 6, 12, and 18 months, respectively. The emergence of these variants was not associated with viral genotype, HBeAg expression status, or pretreatment serum alanine aminotransferase levels. The detection of resistance-associated mutations was observed before the corresponding biochemical flare (41 ± 14 and 60 ± 15 weeks) in the same individuals. Then, if highly sensitive LMV drug resistance testing is carried out at frequent and regular intervals, the relatively long period (19 ± 2 weeks) between the emergence of viral resistance and the onset of biochemical relapse can provide clinicians with ample time to re-evaluate drug therapy.